Sosialisasi Sistem Informasi Inventaris Berbasis Website Sebagai Pendukung Digitalisasi Administrasi RS Darmayu Madiun - Saifulloh Saifulloh; Muhammad Salimy Ahsan; Arul Jeconiah Jaya Pratama; Delta Putra Bagaskara (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service initiative was motivated by logistical administration management issues faced by the partner, Darmayu Hospital. A situational analysis revealed that the partner still relied on conventional inventory recording methods, which were prone to data loss and reduced service efficiency. The practical solution offered by the service team involved technology transfer through outreach and guidance on the use of website-based inventory information systems-specifically SIPITRS and SIMANTIK. The implementation process comprised three participatory stages: (1) identifying partner needs, (2) training and simulation (knowledge transfer), and (3) technical assistance and evaluation. Darmayu Hospital’s administrative and logistics staff participated in the program. The results demonstrated the partner's high level of enthusiasm for adopting the new technology. Significant improvements in capacity and digital literacy were observed, evidenced by a sharp increase in the understanding of system operations—rising from an average of 52.5% prior to training to 88.7% afterward. The initiative concluded that the assistance program successfully empowered staff to transition to digital systems, directly enhancing logistical administration efficiency and improving managerial governance at Darmayu Hospital.